2020
DOI: 10.1155/2020/6279168
|View full text |Cite
|
Sign up to set email alerts
|

Role and Significance of Circulating Biomarkers: miRNA and E2F1 mRNA Expression and Their Association with Type-2 Diabetic Complications

Abstract: Background. Type 2 diabetes mellitus (T2DM) has emerged as an epidemic affecting more than four hundred million people throughout the world. It is a multifactorial disease with range of environmental and genetic factors responsible for its prevalence. In search of novel biomarkers for recording progress of various metabolic diseases, small noncoding RNA in general and microRNAs (miRNAs) in particular have emerged as the most promising biomarkers for diagnosing variety of diseases including diabetes. An increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…IGF2 [494], IRF7 [495], E2F1 [496], TEAD4 [497], KCNH2 [498], E2F2 [499], SNHG7 [500], FLI1 [501], CYP3A5 [502], HMGCS2 [503], GOT1 [504], PPARGC1A [505], GC (GC vitamin D binding protein) [506], VNN1 [507], NOX4 [508], SLC2A1 [509], BPGM (bisphosphoglyceratemutase) [164], NR4A3 [354], PFKFB2 [510], CDH2 [511], F11 [512], AQP2 [513], CLDN2 [514], EGF (epidermal growth factor) [515], ANGPT1 [516], KNG1 [517], SERPINA5 [518], HRG (histidine rich glycoprotein) [519], KL (klotho) [520], DEFB1 [521], ACE2 [522], AQP3 [523], CADM1 [188], DPP4 [524], STC1 [525], REN (renin) [526], TRPM6 [527], MSR1 [528], CCR1 [529], TNFRSF11B [530], FZD5 [531], ERBB4 [216], F8 [532], VCAM1 [533], PTGER3 [534] and ALB (albumin) [535] have been shown to influence the genetic risk of sepsis. IGF2 [536], IRF7 [100], PRKCB (protein kinase C beta) [101], CCL5 [537], EEF1A2 [538], ACTN3 [264], FCN1 [539], BRSK2 [540], MNX1 [541], AMH (anti-Mullerian hormone) [542], E2F1 [543], HAP1 [544], PF4 [545], AGER (advanced glycosylation end-product specific receptor) [546], E2F2 [547], TYMP (thymidine phosphorylase) [548], PPP1CC [549], NR2E1 [550], GREM1 [436], GRIN1 [551], WNT3A [552], COMP (cartilage oligomeric matrix protein) [553], BHMT (betaine--homocysteine S-methyltransferase) [554], ANGPTL3 [555], PCK1 [556], KMO (kynurenine 3-monooxygenase) [557], HSD11B2 […”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF2 [494], IRF7 [495], E2F1 [496], TEAD4 [497], KCNH2 [498], E2F2 [499], SNHG7 [500], FLI1 [501], CYP3A5 [502], HMGCS2 [503], GOT1 [504], PPARGC1A [505], GC (GC vitamin D binding protein) [506], VNN1 [507], NOX4 [508], SLC2A1 [509], BPGM (bisphosphoglyceratemutase) [164], NR4A3 [354], PFKFB2 [510], CDH2 [511], F11 [512], AQP2 [513], CLDN2 [514], EGF (epidermal growth factor) [515], ANGPT1 [516], KNG1 [517], SERPINA5 [518], HRG (histidine rich glycoprotein) [519], KL (klotho) [520], DEFB1 [521], ACE2 [522], AQP3 [523], CADM1 [188], DPP4 [524], STC1 [525], REN (renin) [526], TRPM6 [527], MSR1 [528], CCR1 [529], TNFRSF11B [530], FZD5 [531], ERBB4 [216], F8 [532], VCAM1 [533], PTGER3 [534] and ALB (albumin) [535] have been shown to influence the genetic risk of sepsis. IGF2 [536], IRF7 [100], PRKCB (protein kinase C beta) [101], CCL5 [537], EEF1A2 [538], ACTN3 [264], FCN1 [539], BRSK2 [540], MNX1 [541], AMH (anti-Mullerian hormone) [542], E2F1 [543], HAP1 [544], PF4 [545], AGER (advanced glycosylation end-product specific receptor) [546], E2F2 [547], TYMP (thymidine phosphorylase) [548], PPP1CC [549], NR2E1 [550], GREM1 [436], GRIN1 [551], WNT3A [552], COMP (cartilage oligomeric matrix protein) [553], BHMT (betaine--homocysteine S-methyltransferase) [554], ANGPTL3 [555], PCK1 [556], KMO (kynurenine 3-monooxygenase) [557], HSD11B2 […”
Section: Discussionmentioning
confidence: 99%
“…The identified hub gens, TFs and miRNAs might be involved in the pathological process of AKI. PPP1CC [549], E2F1 [543], EEF1A2 [538], VCAM1 [626], CDH1 [622], AGTR1 [79], SNCA (synuclein alpha) [574], hsa-mir-221 [780], YY1 [781], STAT3 [782] and PDX1 [783] are closely involved with diabetes mellitus. E2F1 [110], BMI1 [95], EEF1A2 [104], ACTA1 [128], VCAM1 [220], AGTR1 [58], hsa-mir-221 [784], MEF2A [785], FOXC1 [786], YY1 [787], STAT3 [788] and BRCA1 [789] were significantly associated with cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of hub genes, miRNA and TF in the pathogenesis of T2DM are discussed. Hsa-mir-142-5p , 235 hsa-mir-1291, 236 NOTCH1 , 237 PPARD (peroxisome proliferator-activated receptor delta), 238 HIF1A , 239 RUNX2 , 240 and E2F1 241 levels are correlated with disease severity in patients with T2DM. Previous studies have demonstrated that hsa-mir-216b-5p 242 and hsa-mir-200a-3p 243 appears to be expressed in Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of hub genes, miRNA and TF in the pathogenesis of T2DM are discussed. Hsa-mir-142-5p [231], hsa-mir-1291 [232], NOTCH1 [233], PPARD (peroxisome proliferator-activated receptor delta) [234], HIF1A [235], RUNX2 [236] and E2F1 [237] levels are correlated with disease severity in patients with T2DM. Previous studies have demonstrated that hsa-mir-216b-5p [238] and hsa-mir-200a-3p [239] appears to be expressed in type 1 diabetes, but these genes might be novel target for T2DM.…”
Section: Discussionmentioning
confidence: 99%